Implementation of the Principle of Constitutional Supremacy in Law Enforcement in Indonesia - Kevin Mario Immanuel; Andri Rahmat Isnaini; Mohammad Solekhan; Yusuf (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
The principle of constitutional supremacy serves as a foundational cornerstone within Indonesia’s legal and governmental framework, positioning the 1945 Constitution of the Republic of Indonesia (UUD NRI 1945) as the highest authority in the hierarchy of legislation. This supremacy is not merely symbolic; it acts as a fundamental norm (grundnorm) that should guide both the legislative process and the execution of state power. This article explores how the principle of constitutional supremacy is applied in the enforcement of law in Indonesia, while also highlighting the normative and structural challenges that hinder consistent constitutional adherence. Utilizing a normative juridical approach, this study analyzes statutory regulations, Constitutional Court rulings, and observes state practices. The findings reveal that despite the Constitutional Court’s significant role in safeguarding constitutional integrity through judicial review, implementation at the practical level often suffers from regulatory inconsistencies, non-compliance with constitutional rulings, and limited constitutional understanding among law enforcers and lawmakers. To address these issues, institutional strengthening, legislative reform, and widespread constitutional education are imperative to ensure all state actions and policies are in harmony with the principle of constitutional supremacy.